ناهد حازم الحيدري تحضير وتشخيص معقدي النحاس(II) والنيكل (II) مع ليكاند مستخلص من مبيد زراعي O,O-diethyl-O-1-phenyl-1H-1,2,4-triazol-3yl-phosphorothioate - الحيدريناهد (University of Thi-Qar Journal of Science, 2019)
New complexes of copporous(II) and nickel(II) ions was prepared by using isolated ligands "O,O-diethyl-O-1-phenyl-1H-1,2,4-triazol-3yl-phosphorothioate"these ligands are used as insecticidal in the agrigulture in which canbe isolated and purified according to the criteria of the specialized company itself that producing it. Of these ions ,new complexes was prepared,.with metal ions by the formation of coordinating links in the linking position that are expected in the isolated ligand to the nitrogen and sulfur ions the copporous(II) compex give greenish colour .while nickel(II)complex give dark green colour. The identification of these prepared complexes by studying the spectroscopic properties of the ultra violet, infrared ,visible and magnetic nuclearresonance waves. This study show identical spectroscopic properties with thr expected structures of the under studying complexes.